Shaping the future : middle schools (Impact on education series, 1998)
This book presents those facilities that best meet the needs of contemporary middle school programs by allowing: teaming; an integration of curriculum initiatives; block scheduling; and an increased focus on such areas as advanced technology, physical fitness and wellness, and consumer science. It documents how the buildings can contribute to the learning process, based on the experiences of nearly 200 middle school administrators, teachers, students, and community members, by providing their insights, ideas, and concerns regarding the role of the school building in successfully reaching students. (GR)